The impact of photo images as propaganda for peace / Kamarudzaman Md. Isa, Mustaffa Halabi Hj. Azahari and Adzrool Idzwan Hj. Ismail - Md. Isa, Kamarudzaman; Azahari, Mustaffa Halabi; Ismail, Adzrool Idzwan (Centre for Media and Information Warfare Studies, 2008)
'Image' to an extent relates with visual representation, which consists of an act of seeing which establishes places or subject matters in the surrounding world; these would in part, describe in words and explaine such paradigm, but yet lacking in the content of the emotional experience as a total. The relation between what is seen and what is known could never achieve as a fulfilled settled communication process. A known representative of imageries, the photography, is known for its implementation within the media or as a medium of persuasion. Such form of images plays an important role, yet lacking the awareness of its motivations or agendas. The production of images as a form of communication to the viewers is a critical process. This paper explores the problems in understanding of photography imageries and their impact.